Emerging outcomes of water vapor thermal therapy (Rezum) in a broad range of patients with lower urinary tract symptoms secondary to benign prostatic hyperplasia: A systematic review. Issue 3 (1st March 2022) - Babar, Mustufa; Loloi, Justin; Tang, Kevin; Syed, Umar; Ciatto, Michael
Abstract: Water vapor thermal therapy (Rezum) is a novel, minimally invasive surgical technology used to treat lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). The objective of this systematic review is to evaluate the latest efficacy and safety profile of Rezum in patients with LUTS secondary to BPH. PubMed/MEDLINE and the Cochrane Library databases were systematically searched, in accordance with the PRISMA statement, for relevant articles in the English language till 1 August 2021. Randomized and nonrandomized studies that evaluated urinary outcomes and/or adverse events were deemed eligible. Nineteen studies (N = 1942), published in 25 articles, were included. International Prostate Symptom Score (IPSS), quality of life (QoL), and maximum urinary flow rate (Qmax) significantly improved as early as 1 month postoperatively and remained durable for up to 5 years. Significant median percent improvements in IPSS, QoL, and Qmax at 3 months were 51%, 51%, and 66%, respectively. Patients with obstructive median lobes, large prostates (>80 g), small prostates (<30 g), and urinary retention also experienced significant relief in LUTS, with 83% of urinary retention patients becoming catheter independent at a median of 14 days. Most adverse events were transient and nonserious and occurred in 0% to 76% of patients (median 29%), with de novo erectile dysfunction rates ranging between 0% and 3.1%. Surgical retreatment rate ranged between 4.4% and 7.5% at 5 years postoperatively. Rezum provides durable improvements in symptoms, irrespective of prostate volume and urinary retention status, and has low rates of sexual dysfunction.